Enhancing Protein Recovery in Green Biorefineries by Lignosulfonate-Assisted Precipitation - la Cour, Rasmus; Schjoerring, Jan K.; Jørgensen, Henning (Frontiers in Sustainable Food Systems, 2019)
Biorefining of green biomass to produce proteins for feed and food provides an important challenge in relation to development of a future sustainable and climate-neutral agriculture. In order to make it a viable value chain, all parts of the process need to be optimized. This includes careful selection of the source of biomass, the procedure used for protein extraction as well as the separation and recovery of proteins from the press juice. We here focus on recovery of proteins from juice made from screw press fractionation of four green biomasses, viz. ryegrass, red clover, ryegrass-white clover mixture and spinach. Separating out protein from the juice is a key step and several different methods have routinely been applied. We demonstrate that lignosulfonates aid in the precipitation of proteins in the juice. The optimal loading of lignosulfonate was 0.6-0.7 g per g crude protein in the juice. For ryegrass and red clover juice, this loading resulted in 10-25 % increase in precipitated protein compared to the classical precipitation by heat treatment or acidification. For spinach, up to 60% increase in protein recovery was obtained by lignosulfonate addition. We conclude that lignosulfonate-assisted precipitation holds potential for improving the protein yield in biorefining of green biomass.